Chemical diversity in leaf and stem essential oils of Origanum vulgare L. and their effects on microbicidal activities - Merajuddin Khan (AMB Express, 2019)
Abstract Essential oils (EOs) from the stems and leaves of Origanum vulgare L. grown in Saudi Arabia and Jordan were analyzed by gas chromatography–mass spectrometry (GC–MS) and GC–flame ionization detector (FID) techniques on two different columns (polar and nonpolar). A detailed phytochemical analysis led to the identification of 153 constituents of these essential oils. Both Saudi and Jordanian plants are classified by chemotypes rich in cymyl-compounds. However, the Saudi Origanum contains carvacrol as the major component and is, thus, characterized as a carvacrol chemotype, while the Jordanian Origanum contains thymol as the major component, and, thus, it is classified as a thymol chemotype. In addition, the antimicrobial activities of the studied EOs and their major components, including carvacrol and thymol, were evaluated against various Gram-positive and Gram-negative microorganisms. All the tested compounds exhibited significant antimicrobial activity against all the tested bacteria. Among them, thymol demonstrated superior activity against all the tested organisms, followed by carvacrol. Moreover, results on oil composition and oil yield of O. vulgare L. from different parts of the world is compared in detail with the present outcomes.